Inalienable Customer Capital, Corporate Liquidity, and Stock Returns - DOU, WINSTON WEI; JI, YAN; REIBSTEIN, DAVID; WU, WEI (Journal of Finance, 2021)
ABSTRACT We develop a model in which customer capital depends on key talents' contribution and pure brand recognition. Customer capital guarantees stable demand but is fragile to financial constraints risk if retained mainly by talents, who tend to quit financially constrained firms, damaging customer capital. Using a proprietary, granular brand‐perception survey, we construct a firm‐level measure of the inalienability of customer capital (ICC) that captures the degree to which customer capital depends on talents. Firms with higher ICC have higher average returns, higher talent turnover, and more precautionary financial policies. The ICC‐sorted long‐short portfolio's spread comoves with financial constraints factor.